Sampled-data-based consensus of multi-agent systems under asynchronous denial-of-service attacks. (February 2021) - Liu, Hao; Wang, Zhujun
Abstract: This paper investigates the sampled-data-based consensus problem of multi-agent systems (MASs) under asynchronous denial-of-service (DoS) attacks. In order to describe asynchronous DoS attacks, a new definition of complete DoS attack and novel double-layer switched systems are proposed. A complete DoS attack refers to a DoS attack that consists of several consecutive successful DoS attacks. While a successful DoS attack denotes an attack that can break the connected communication topology into several isolated subgraphs. Based on this, the original system is transformed into a double-layer switched systems with a stable mode and several unstable modes. It should be pointed out that each unstable subsystem is also composed of finite second-level unstable subsystems that represent consecutive successful DoS attacks. Moreover, a new double -mode-dependent Lyapunov function (DMDLF) method is employed to obtain the lower and upper bounds of the corresponding average dwell time (ADT) of subsystems. It is proved that the consensus of MASs under asynchronous DoS attacks can be achieved by using the feedback consensus controllers which can be designed simultaneously. Finally, an illustrative example is provided to illustrate the effectiveness of the results proposed in this paper.